Analisis pengaruh pelatihan dan kepemimpinan terhadap kinerja karyawan - Ayu Puspitasari; Adissya Maya Andara; Miranti Putry; Mela Sandra (Amal Insani Foundation, 2022)
Human resources are a determining factor in achieving company goals. With these, human resources are required to be professional to achieve the targets and progress of the company so that they are superior to competitors. This type of research is a quantitative study to find out the effect of training and leadership on employee performance at Ramayana Mall Serang. The population in this study amounted to 63 employees, while the sample used was the saturated sample technique, which means that the entire population was sampled. The primary data used is through the distribution of questionnaires which are distributed directly to the respondents. The tool used to analyze the data obtained is using the help of SPSS software. The results showed that training and leadership either partially or simultaneously significantly affected employee performance. Ramayana Mall Serang is advised to pay attention and improve training and leadership to improve the quality of employee performance more optimally.